PROSES KATALITIK DISTILAT MINYAK BATUBARA BANKO SELATAN DENGAN HYDROTREATMENT SATU TAHAP DAN DUA TAHAP - Murti, Sri Djangkung Sumbogo (Badan Pengkajian dan Penerapan Teknologi, 2008)
Catalytic hydrotreatment of South Banko coal liquid (SBCL) distillates wasstudied through single and two-stage hydrotreatment over a commercialNiMo/Al2O3 catalyst. The hydrotreatment was conducted in an autoclave of 50 mlcapacity under the conditions of 360 ? 450 oC and 30 ? 120 min at initialhydrogen pressure of 10 MPa. The hydrotreatment reduced the contents of allhetero-atom species (S, N and O). sulfur species were easiest to be removedeven at low temperature of 360 oC. In contrast nitrogen species were mostrefractory. The higher temperature and more amount of catalyst enhanced thedenitrogenation reaction. The two-stage hydrotreatment was more effective forthe denitrogenation and deoxygenation because of the fresh hydrogen in thesecond stage and the combination of lower and higher reaction temperature ateach stage.Kata kunci: hydrotreatment katalitik, heteroatom, single and two stagehydrotreatment, katalis, desulfurisasi, denitrogenasi,deoksigenasi, GC-AED